👤

x+7=x^2-49
<=> x+7= (x+....)(x-7)
<=>(x+7)-(x+...)(x-7)=.....
<=>(x+7)(....-(x-7))=.....
<=>(x-7)(.......)=......
Merci !


Répondre :

Bonjour,

x+7=x²-49 <=> x+7=(x+7)(x-7)
                 <=> (x+7)-(x+7)(x-7)=0
                 <=> (x+7)(1-(x-7))=0
                 <=> (x+7)(8-x)=0

Donc (x+7)=0        ou        (8-x)=0
           x=-7            ou         x=8

S={-7;8}

Vérification : -7+7=0 et 7²-49 =0 
        
                     8+7=15 et 8²-49=15

8 et -7 sont donc bien solutions.